2020
DOI: 10.9734/ajrid/2020/v4i130137
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors for Pulmonary Tuberculosis Incidence in Ghana: A Small Matched Case-control Study

Abstract: Aims: Knowing the risk factors for tuberculosis (TB) opens up avenues for identifying target groups for intensified case finding. We aimed to identify the risk factors for pulmonary TB (PTB) incidence in a rural district in northern Ghana. Study Design: A matched case-control study. Place and Duration of Study: The Kassena Nankana West District of the Upper East Region of Ghana, between February 2019 and March 2019. Methodology: This study was conducted in 4 public health facilities. Cases we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Similarly, other studies in Africa [23,26], found that TB patients are stigmatized against in their community and peers. Reported forms of stigmatization includes friends and neighbours looking down upon TB patients; friends or neighbours looking down on TB patients' family; and friends or neighbours avoiding TB patients on purpose [26][27][28]. The high level of stigmatization in the community could affect case detection as people would not report for testing or default treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies in Africa [23,26], found that TB patients are stigmatized against in their community and peers. Reported forms of stigmatization includes friends and neighbours looking down upon TB patients; friends or neighbours looking down on TB patients' family; and friends or neighbours avoiding TB patients on purpose [26][27][28]. The high level of stigmatization in the community could affect case detection as people would not report for testing or default treatment.…”
Section: Discussionmentioning
confidence: 99%